2017
DOI: 10.3846/16111699.2017.1279683
|View full text |Cite
|
Sign up to set email alerts
|

Proposing an Agile Strategy for a Steel Industry Supply Chain Through the Integration of Balance Scorecard and Interpretive Structural Modeling

Abstract: The internal and external environment of all organizations challenges them adapt to the best practices and reconsider their relationship throughout the supply chain. In this paper, the authors have tried to propose an agile strategy for the supply chain of a steel company, which ranks 3 rd in Iran in Gross Sale with 16,000 employees, in order to respond quickly to ever-changing needs. To do this, through the literature review the framework of balanced scorecard was utilized to structure agility factors in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Business performance measurement is a topical issue in strategic management, and thus more research regarding this topic can be expected (Tizroo et al, 2017;Petera, Wagner, & Menšík, 2012;Horváthová et al, 2014;Becerra-Alonso, Androniceanu & Georgescu, 2016;Łakomy-Zinowik& Horváthová, 2016;Gumbus & Lussier, 2006). Enterprises are largely managed through financial indicators, but the current trend is showing the increasing importance of non-financial measurers, too.…”
Section: Resultsmentioning
confidence: 99%
“…Business performance measurement is a topical issue in strategic management, and thus more research regarding this topic can be expected (Tizroo et al, 2017;Petera, Wagner, & Menšík, 2012;Horváthová et al, 2014;Becerra-Alonso, Androniceanu & Georgescu, 2016;Łakomy-Zinowik& Horváthová, 2016;Gumbus & Lussier, 2006). Enterprises are largely managed through financial indicators, but the current trend is showing the increasing importance of non-financial measurers, too.…”
Section: Resultsmentioning
confidence: 99%
“…Maintenance and repair costs are proportional to the distance traveled by the vehicles, so in this case, they are valued at EUR/km. The tolls for the different modes of transport are calculated according to different methodologies [48,50].…”
Section: Structure Of Indicators Of Functional Dependencies Between the Main Transport Processmentioning
confidence: 99%
“…For setting the goal, it used the pre-emptive priority goal programming modeling where a deviation from a higher priority level goal is considered to be infinitely more important than a deviation from a lower priority goal [50]. The quality of the freight process is determined by three key indicators: cost, time, and reliability, which also includes security.…”
Section: Setting the Goal Functionmentioning
confidence: 99%
“…Agility provides to both internal and external efficiency for the companies. Tizroo, Esmaeili, Khaksar, Šaparauskas, and Mozaffari (2017) presents the agility factors for the steel industry supply chain and are grouped these factors within the four perspectives of the BSC. They suggested that agility related factors should be integrated and adopted into four perspectives to the BSC.…”
Section: Need For Agile Perspectivementioning
confidence: 99%